PROJECTING VISUALISATION OF DIDACTIC OBJECTS AS A DETERMINANT OF STUDENTS’ DEVELOPMENT - N. N. Manko (Образование и наука)
The paper investigates the pedagogic potential of visualization phenomenon. The research is aimed at substantiating the didactic instruments implementation for raising the effectiveness of knowledge acquisition. The research methodology basis incorporates the cognitive visualization ideas along with the theory and technology of instrumental didactics.The projection process, viewed as the mechanism and outcome of the human mind activity, is regarded as a pedagogic means for visualization and modeling of educational content. For organizing and controlling the above process, the author introduces a regulative concept, referred to as the programming basis of a human consciousness directing the cognition processes and reflecting the outcomes of teaching activity.The development trends of pedagogic principle of visibility are demonstrated; the projective regulative visualization of didactic objects being outlined. The author describes the anthropological and socio-cultural background of visibility principle and suggests the complex of didactic visual means for solving the pedagogic tasks.